Interpretation of Qur'anic Economics with a Thematic Interpretation Approach in Overcoming Digital Debt and Dependence on Controversial Online Financial Services on E-Economy Platforms - Mukhtar Yunus (Journal AGENCY, 2023)
Digital transformation has revolutionized the global economic landscape, including in Indonesia, with the emergence of e-economy platforms providing online financial services such as pay later, buy now pay later (BNPL), and peer-to-peer lending. Although this technology offers easy access to capital and consumption, the phenomenon of digital debt and reliance on controversial online financial services has become a serious threat to public welfare. Many users, especially the younger generation and the lower-middle class, are trapped in a debt spiral that is difficult to break due to predatory lending practices, high interest rates, and psychological mechanisms deliberately designed to create dependency. In this context, this paper examines the potential interpretation of Qur'anic economics through a thematic exegesis (thematic interpretation) approach as an ethical and theological foundation to address digital debt issues. This study is a library research with a qualitative approach that analyzes Qur'anic verses related to economics, debt, and consumptive behavior using the thematic exegesis method. The results indicate that the Qur'an provides a comprehensive ethical framework encompassing the principles of justice in transactions (al-'adl), the prohibition of usury (al-riba), responsible debt management, as well as the concepts of qana'ah (contentment) and islah (balance) which can serve as the foundation for digital financial regulation and literacy. These findings offer a theoretical contribution to the development of the digital Sharia economy and provide policy recommendations for regulators, fintech platforms, and the public in facing contemporary e-economy challenges.